The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1037/a0033700
|View full text |Cite
|
Sign up to set email alerts
|

Learned predictiveness influences rapid attentional capture: Evidence from the dot probe task.

Abstract: Attentional theories of associative learning and categorization propose that learning about the predictiveness of a stimulus influences the amount of attention that is paid to that stimulus. Three experiments tested this idea by looking at the extent to which stimuli that had previously been experienced as predictive or nonpredictive in a categorization task were able to capture attention in a dot probe task. Consistent with certain attentional theories of learning, responses to the dot probe were faster when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
121
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(153 citation statements)
references
References 43 publications
23
121
0
Order By: Relevance
“…In agreement with this idea, recent research has found that human participants spent more time looking at good predictors than looking at poor predictors (Le Pelley, Beesley, & Griffiths, 2011; but see Hogarth et al 2008). Human participants have also found to show faster reaction times to predictive than to non-predictive cues (Le Pelley, Vadillo, & Luque, 2013). However, it is also true that in situations with high level of uncertainty participants spent more time looking at cues which results are uncertain (Beesley, et al, 2015).…”
mentioning
confidence: 69%
“…In agreement with this idea, recent research has found that human participants spent more time looking at good predictors than looking at poor predictors (Le Pelley, Beesley, & Griffiths, 2011; but see Hogarth et al 2008). Human participants have also found to show faster reaction times to predictive than to non-predictive cues (Le Pelley, Vadillo, & Luque, 2013). However, it is also true that in situations with high level of uncertainty participants spent more time looking at cues which results are uncertain (Beesley, et al, 2015).…”
mentioning
confidence: 69%
“…Our interest in this effect was motivated by the possibility of obtaining a more specific characterization of attentional changes during learning than can be obtained using indirect measures. Already it was , 2013;Wills et al, 2007;Wilson et al, 1992) supposed that the learning rates for both CSn and CSr were adjusted to a lower limiting value, hence their equivalence. However, additional explanation is still required for the failure to see a significant difference between CSp and CSr.…”
Section: Discussionmentioning
confidence: 99%
“…Already it was known that stimulus sampling and visual attention changes can occur (e.g. Kruschke, Kappenman, & Hetrick, 2005;Le Pelley et al, 2013;Wills et al, 2007;Wilson et al, 1992) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Although the difference between CSp and CSn on AB in Experiment 2 was clear some comments on the methodology and theoretical interpretation are warranted. We attribute the difference in the results of Experiments 1 and 2 to the increased weighting of relative prediction error consequent to the introduction of distinctive comparator stimuli in the RSVP stream.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations